Auditiv berikning till lappuggla (Strix nebulosa) på Nordens Ark : att stimulera jaktbeteenden - Sandberg, Emelie (SLU/Dept. of Animal Environment and Health (until 231231), 2016)
Owls are efficent predators with a well developed auditory system adapted to localize the exact position of the prey. In captivity owls rarely get the chance to perform their hunting behaviour. Very few studies has been made on owls in captivity and none about environmental or behavioural enrichment. In BIAZA’s Owl Management Guidelines there is a small chapter about behavioral enrichment describing the lack of knowledge on the subject and emphasizing the importance of more research and the introduction of enrichment into the keeping routine. This study was performed on two Great grey owls (Strix nebulosa lapponica) at Nordens Ark in Bohuslän, Sweden for twelve days. The aim of this study was to investigate whether enrichment of a recorded sound of a prey animal could stimulate the owls’ hunting behavior. The aim was also to consider the possibility of feeding in the night using an automatic food dispenser to promote natural foraging behavior. Three different treatments were presented to the owls combined with four control days without enrichmet. A food dispenser, PetPod for cats, was used and placed in two different locations, combined with the recorded sound of a house mouse. The various treatments were (1.) LJ , sound enrichment - only sound was presented to the owls; (2.) VM, audio- and feed enrichment - presented the sound in combination with feed from PetPod hung on a pillar inside the aviary; (3.) MP, audio- and feed enrichment - presented the same things as VM but from the ground inside the aviary. The results showed that the owls activity increased by all treatments compared to the control. It also showed that the owls hunting behavior increased considerably and they also attacked the food from PetPod in a natural way. MP was the presentation that triggered the strongest responses and there is potential to feed the owls at night automatically in that way. Futher studies are required to refine the methods and learn how the responses to the sound enrichment develop over time.